JUG WITH ZOOMORPHIC HANDLE FROM THE BURIAL MOUND 1577 OF THE PALASA-SYRT BURIAL GROUND OF THE IV-V CENTURIES - Magomedov, U A (History, Archeology and Ethnography of the Caucasus, 2015)
The article deals with a rare type of jugs of the Palasa-Syrt burial mound of the 4th–5th cc. – the jug with the handle in the form of an animal figurine. The jug was among the grave goods of a rich woman’s burial (mound 1577), studied in 2015. The author of the article has pointed out technological methods of production of the vessel, conducted comparative analysis of the similar vessels from this burial mound, attempted to justify the rarity of vessels with zoomorphic handles in the ceramic collection of the burial mound.
Keywords: jug with zoomorphic handle; Palasa-Syrt burial mound; burial 1577